PENANAMAN JIWA GUSJIGANG PADA SANTRI - Hadi, Nur; Mulyono, Puput (Tahta Media Grup, 2024)
The purpose of this service is to find out the local wisdom of Gusjigang for santri. The method in this research is a case study to reveal the reality of gusjigang for santri, with the hope of revealing the benefits of gusjigang for santri and increasing the economic independence of santri. Gusjigang, as an example of the entrepreneurial spirit of santri, is expected to be able to overcome the character of capitalism which always seeks profit but sacrifices social morals. The spiritual strength of the santri community with a gusjigang spirit can increase a positive trade ethos. The local content of gusjigang is not yet in the curriculum at the Daarul Huda Salafiyah Islamic Boarding School, Sukoharjo, Central Java. A big challenge for the service team is to start introducing the importance of the gusjigang spirit to students at the Daarul Huda Salafiyah Islamic Boarding School, Sukoharjo, Central Java.